2023
DOI: 10.1111/1759-7714.14856
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic zinc finger protein ZNF687 accelerates lung adenocarcinoma cell proliferation and tumor progression by activating the PI3K/AKT signaling pathway

Abstract: Background Zinc finger protein 687 (ZNF687) has previously been discovered as a potential oncogene in individuals with giant cell tumors of the bone, acute myeloid leukemia, and hepatocellular carcinoma. However, its role and mechanism in lung adenocarcinoma (LUAD) remain unclear. Methods In LUAD cells, tumor, and matched adjacent tissue specimens, quantitative real‐time RT‐ polymerase chain reaction (qRT‐PCR), western blotting analyses, and immunohistochemistry stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…ZNF687 has been confirmed to be a facilitator in the progression of some cancers, [13][14][15][16] but its regulatory functions in CRC maintain dimness. This study found that ZNF687 had a higher expression in CRC tissues and cells, which contributed to the poor prognosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZNF687 has been confirmed to be a facilitator in the progression of some cancers, [13][14][15][16] but its regulatory functions in CRC maintain dimness. This study found that ZNF687 had a higher expression in CRC tissues and cells, which contributed to the poor prognosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…13 Furthermore, ZNF687 activates the PI3K/AKT pathway to aggravate tumorigenesis in lung adenocarcinoma. 14 In addition, studies have indicated that ZNF687 exhibits higher expression and mutates in bone cancer and acute myeloid leukemia through its oncogenic function. 15,16 Nevertheless, no research has been investigated on the regulatory functions of ZNF687 in CRC progression.…”
Section: Introductionmentioning
confidence: 99%